2010
DOI: 10.1002/jbm.b.31752
|View full text |Cite
|
Sign up to set email alerts
|

Controllable dual‐release of dexamethasone and bovine serum albumin from PLGA/β‐tricalcium phosphate composite scaffolds

Abstract: Localized dual-drug delivery from biodegradable scaffolds is an important strategy in tissue engineering. In this study, porous poly(L-lactide-co-glycolide) (PLGA)/β-tricalcium phosphate scaffolds containing both dexamethasone (Dex) and bovine serum albumin (BSA) were prepared by incorporating Dex-loaded and BSA-loaded microspheres into the scaffolds. PLGA microspheres containing Dex or BSA were prepared by spray-drying and double emulsion/solvent evaporation, respectively. In vitro release studies indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…In previous studies, it was reported that the incorporation of bone substitutes with microspheres demonstrated an initial burst release in the first days, which was followed by slower release kinetics as the microspheres biodegraded . In the current study, the release profile suggested that the microspheres released around 50% of clarithromycin during the first week.…”
Section: Discussionsupporting
confidence: 56%
“…In previous studies, it was reported that the incorporation of bone substitutes with microspheres demonstrated an initial burst release in the first days, which was followed by slower release kinetics as the microspheres biodegraded . In the current study, the release profile suggested that the microspheres released around 50% of clarithromycin during the first week.…”
Section: Discussionsupporting
confidence: 56%
“…Drugs or proteins especially growth factors or genes to express growth factors were also loaded into porous scaffolds, which could significantly improve the regeneration of new tissues [12,55,75,83,84].…”
Section: Tissue Repair and Reconstruction Based On Poly(lactide-co-glmentioning
confidence: 99%
“…The electrospun scaffold possesses high specific surface area, high porosity and an interconnected pore network, which is similar architecturally to the natural ECM and can enhance the adhesion and growth of cells . The development of a porous scaffold, capable of controlling local delivery of bioactive agents, to promote cell behavior and facilitate tissue restoration is one of the major purposes of tissue engineering …”
Section: Introductionmentioning
confidence: 99%